Action Games Evolution Analysis: A Case Study Using the God of War Series - Zeliang Zhang; Naying Gao; Siqi Li; Mohd Nor Akmal Khalid; Hiroyuki Iida (IEEE Access, 2022)
Technology advancements allowed the development of action games that packed multifaceted play in a single game while requiring fast-paced movements. Since modern action game is composed of boss battles, evaluating them was scarcely investigated. In this study, the analysis of the boss battle was conducted based on the God of War (GoW) series, where the underlying entertainment aspects of the game were identified. The information progress of the boss battle of each of the considered GoW series was modeled using the game refinement (GR) theory and its extension, called motion in mind. The evolution of challenge, anticipation, and unpredictability between different GoW series was identified while the entertainment aspects of the game were investigated. The evolutionary trend of the sophistication and unpredictability of the GoW series games provided insights into the intended narrative design, harmonic balance between skill and chance, and provided learning comfort for player mastery of the game-playing.